Sistem Pengendalian Nutrisi Hidroponik Menggunakan Logika Fuzzy Berbasis Internet of Things - Fauzan, Farhan; Lesmana, Iwan; Nugraha, Nunu (Algoritme Jurnal Mahasiswa Teknik Informatika, 2025)
Hydroponics, using water instead of soil for cultivation, often faces nutrient instability issues. This research developed an IoT-based nutrient control system using the Mamdani Fuzzy Logic algorithm to maintain nutrient stability for optimal plant growth. The system includes a microcontroller, sensors, and the Fuzzy Logic algorithm, tested through a prototype. Results showed the system effectively maintained nutrient stability, with pH levels between 5.5 and 6.5 and Total Dissolved Solids (TDS) between 650 and 850. Pumps adjusted based on nutrient conditions, demonstrating good performance. This Fuzzy Logic-based control system is ready for widespread use, ensuring reliable nutrient stability for hydroponic plants.